Can the French Paradox be Achieved with the Drinking of Palm Wine? - Ordinioha, Best; Brisibe, Seiyefa (The Nigerian Health Journal, 2015)
Background: As the prevalence of non-communicable diseases continues to increase in Nigeria, efforts at finding effective control measures should extend to seemingly contradicting areas. Palm wine is widely drank in southern Nigeria, for recreational and health reasons, often serving as a social lubricant. This review article explored the likelihood of achieving the French paradox with palm wine, for the prevention and management of the emerging non-communicable diseases.Material and Methods: Data for the review were collected from peer review journals and include information on the composition and fermentation process of the wine, the health implications of the constituents, and the information required to repackage and market the wine to meet the objectives.Results: Palm wine is a heavy suspension of largely non-pathogenic yeasts and bacteria that do not support the growth of most pathogenic organisms. It is made up of more than 90% water, 4.14% carbohydrate, 0.14% protein, several minerals, some flavonoids and a variable concentration of alcohol. The polyphenol content of palm wine is comparable with those of conventional wine, and palm wine has been shown to cause up to a 21.8% decrease in gastric acid secretion, hence can be useful for peptic ulcer patients. Palm wine also has some anti-sickling properties, and the ability to reduce the osmotic fragility of the sickle cell, which can be beneficial to patients with sickle cell disease.Conclusion: Palm wine has several health benefits that can be harnessed for the control of the non- communicable diseases, especially if it is stopped from fermentation. The low alcoholic palm wine should therefore be promoted for widespread use, using the social marketing technique.